High potential of adhesion to biotic and abiotic surfaces by opportunistic Staphylococcus aureus strains isolated from orthodontic appliances. (February 2016) - Merghni, Abderrahmen; Ben Nejma, Mouna; Dallel, Ines; Tobji, Samir; Ben Amor, Adel; Janel, Sébastien; Lafont, Frank; Aouni, Mahjoub; Mastouri, Maha
Abstract: Orthodontic and other oral appliances act as reservoir of opportunistic pathogens that can easily become resistant to antibiotics and cause systemic infections. The aim of this study was to investigate the ability of Staphylococcus aureus strains isolated from healthy patients with orthodontic appliances, to adhere to biotic (HeLa cells) and abiotic surfaces (polystyrene and dental alloy). Adhesive ability to polystyrene was tested by crystal violet staining and quantitative biofilm production on dental alloy surfaces was evaluated by MTT reduction assay. In addition, the presence of ica A and ica D genes was achieved by polymerase chain reaction (PCR). Qualitative biofilm production revealed that 70.6% of strains were slime producers. The metabolic activity of S. aureus biofilms on dental alloy surfaces was high and did not differ between tested strains. Moreover, all the isolates were adhesive to HeLa cells and 94% of them harbor ica A and ica D genes. Considerable adhesion and internalization capacity to the epithelial HeLa cells and strong biofilm production abilities together, with a high genotypic expression of ica A/ ica D genes are an important equipment of S . aureus to colonize orthodontic appliances and eventually to disseminate towards other body areas. Highlights: S. aureus strains were isolated from orthodontic appliances. S. aureus isolates showed a high potential of adhesion to biotic and abiotic surfaces. The majority of S. aureus strains were positive for ica A and ica D genes.